Acehnese lexical and grammatical collocations of the North Aceh dialect - Kismullah Abdul Muthalib; Siti Rahmah; Zulfadli A. Aziz (Universitas Syiah Kuala, 2022)
This research dealt with collocations used in the North Aceh dialect. It analyzed the part of speech categories into which collocations of the North Aceh dialect can be grouped. This research focused on the grammatical collocations and lexical collocations used in the Blang Mee village of Bireuen District, Aceh, Indonesia. This is a descriptive qualitative using case study looking into the villagers’ use of Acehnese collocations. Six Acehnese speakers were selected as the language informants. They were fifty years old or above and never traveled or lived outside of Blang Mee. Data were extracted from interviews with these speakers who were asked to discuss general topics in Acehnese. The analysis was performed using a framework on collocation categories by Benson et al. The results of the analysis showed both lexical and grammatical collocations used by speakers in North Aceh. Lexical collocations were found in the forms of verb (denoting creation or activation) + noun combinations, verb (meaning eradication or nullification) + a noun, adjective + noun combinations, noun + verb combinations, noun + noun combinations, adverb + adjective combinations, and verb + adverb combinations. Grammatical collocations came in the following combinations: noun + preposition combinations, adjective + preposition combinations, preposition + noun combinations, and collocational verb patterns. The collocations used by the North Aceh dialect speakers indicate the uniqueness of their dialect within other dialects spoken by the Acehnese.